1977
DOI: 10.2307/3665259
|View full text |Cite
|
Sign up to set email alerts
|

Sales Forecasting Practices of Large U.S. Industrial Firms

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Practitioners, on the other hand, prefer the internal rate of return (IRR) method, as several other studies have revealed. For example, the study of Pan, Nichols, and Joy (1977) presented some evidence regarding the current state of the art of business sales forecasting practices. McDaniel, McCarty, and Jessell (1988), developed an alternative yield-based capital budgeting technique, the marginal return on invested capital (MRIC).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Practitioners, on the other hand, prefer the internal rate of return (IRR) method, as several other studies have revealed. For example, the study of Pan, Nichols, and Joy (1977) presented some evidence regarding the current state of the art of business sales forecasting practices. McDaniel, McCarty, and Jessell (1988), developed an alternative yield-based capital budgeting technique, the marginal return on invested capital (MRIC).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Previous studies include those by Sales Management (1987), Dalrymple (1975), Dalrymple (1987), Mentzer and Cox (1984), Wheelwright and Clarke (1976), Sparkes and McHugh (1984), Rothe (1978), Cerullo and Avila (1975), Pokemper and Bailey (1970), and Pan et al, (1977). These primarily have used only leading business firms, Fortune 500 US firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An additional 28 per cent said forecasting was important although not critical (Dalrymple, 1975). Since sales forecasting is an important input to the corporate planning process, it is not surprising that surveys have been done on the use of forecasting techniques in companies (Dalrymple, 1975; Conference Board, 1970, 1971Pan, Nichols and Joy, 1977;Reichard, 1966; Sales Management, 1967;Wheelwright and Clarke, 1976). A summary of the scope of these surveys is given in Exhibit 1.…”
mentioning
confidence: 99%